The Harmony Pattern through Huma Betang Culture of the Dayak Communities in Central Kalimantan - Adang Nofandi; Ngainun Naim; Rinto Hasiholan Hutapea (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
Indonesia is somewhat affluent with conflict experiences due to differences in various backgrounds. The poorly managed religious, tribal, and cultural heterogeneities have become threats. Accordingly, the harmony amid heterogeneity in Central Kalimantan has become an interesting phenomenon. The harmony has fairly solid foundations, and one of them is the cultural base. This article aims to explore the cultural base that has become the foundation for the creation of harmony and the interaction between the community leaders in building harmony. The method used was qualitative-descriptive using empirical and normative approaches. The data was collected through observations, in-depth interviews, and documentation. They were further analyzed by using Miles and Huberman’s models. This article found that huma betang has become a fairly solid cultural base in preserving community harmony. The interaction between community leaders, religious leaders, and indigenous leaders has become a supporting factor to maintain harmony in Central Kalimantan. This article is still limited to cultural harmony. Therefore, it calls for other perspectives to further enrich and deepen the study.